Peningkatan Hasil Belajar Matematika Kelas III Materi Operasi Pecahan Melalui Metode Learning by Game dengan Media Gambar Pecahan - Martha Bela, Rizky Tri; Sudarmani (LPPM Universitas Terbuka, 2024)
This research aims to improve mathematics learning outcomes regarding fraction operations through the Learning by Game method with fraction pictures for class III students at SDN 1 Petir. This research was carried out in two cycles, each cycle held 2 meetings. Each cycle consists of 4 stages, namely planning, implementation, observation and reflection. This type of research uses classroom action research (PTK). The method used in this research is a descriptive qualitative approach method which was carried out on 20 class III students. Data collection techniques use tests and observations. The research results have increased with the Learning by game method using fractional image media. In cycle I and cycle II there was an increase in learning outcomes from 55% in the first cycle to 90% in the second cycle. The results of this research can be concluded that the application of the learning by game learning model using fraction image media has proven to be able to improve mathematics learning outcomes regarding fraction operations in class III students at SD Negeri 1 Petir in 2024.